Shipwreck Architecture - Simon Weir; Sara Rich (Footprint)
Shipwreck Architecture draws a connection between cosmotechnics, surrealism, and object-oriented ontology using an architectural design framework as a departure point. An academic introduction will connect the tragic aspects of Yuk Hui’s cosmotechnics, to the tragic pairings created by figurative surrealists Rene Magritte and Salvador Dalí, to the ontographic project of shipwreck hauntography. This trajectory of ideas is then projected into a creative project: a speculative history of shipwreck architecture where the cutting edge of biological research is projected into a technological future when the distant aims of today’s technology are ancient history: when the first generations of grown buildings are preserved as ruins, when giant decommissioned carbon-capture factories drift like ghost ships across lakes of their inky waste, when people remember when shipwrecks caused by the hazards of rising sea levels were later exposed by sinking sea levels and converted into hotels and theatres, and finally, when these theatrical memories provoke such nostalgia that shipwreck architecture would be replicated and fabricated.